Embodyment Commedia Dell Arte of in Moliere Script: Cases Study with Le Medecin Malgre Lui - M Andreanda Dwi Putra; Saaduddin Saaduddin; Desi Susanti (SENDRATASIK UNP, 2024)
The play "Le Medecin Malgre Lui" by Moliere, translated by Adi Krishna, is an attempt to criticize the medical practices of Moliere's time, reflecting the ignorance and incompetence of the doctors of that era, represented by the character Sganarele. The Realism style is chosen to approach Moliere's play, but utilizing the Commedia dell'arte method. This play is presented as an option to realize Moliere's desired comedy. This research employs an art practice-based research method through the Commedia dell’arte method, including Observation, Representation, and Improvisation. This is done to find a formula for approaching roles to promote the Commedia dell'arte method systematically. In practice, interdisciplinary approaches that integrate artistic creation with scientific inquiry can explore and convey complex ideas through creative stages realized through the character Sganarelle as the main character in the play Le Medecin Malgre Lui